The Influence of Online Review Vlogger on Tourism Decisions to The Beach in Improving Halal Tourism Awarenes for Milennial Generation - Nanik Wahyuningtiyas; Tri Sugiarti Ramadhan (Universitas Negeri Padang, 2020)
This study aims to analyze and explain (1) To determine the effect of Attractiveness, Trustworthiness, Expertise partially influential on Tourism Decisions; (2) To find out the influence of Attractiveness, Trustworthiness, Expertise simultaneously influence on Tourism Decisions; (3) To determine the effect of Attractiveness, Trustworthiness, Expertise partially influence Awareness; (4) To find out the influence of Attractiveness, Attractiveness, Trustworthiness, Expertise simultaneously influence on Awareness; (5) To determine the effect of Tourism Decisions have an effect on Awareness; (6) To find out the influence of Attractiveness, Trustworthiness, Expertise partially influence Awareness through Tourism Decisions as an intervening variable.This study uses a data collection method with a questionnaire, with a quantitative approach. The population that is the object of research is tourists visiting the South Malang Coast region. Testing the analysis using path analysis.The results of this study indicate (a) Partial testing of variables consisting of attractiveness, trustworthiness, expertise that affect travel decisions viewed from the significant value is attractiveness. (b) Simultaneous test results of variables consisting of attractiveness, trustworthiness, expertise that affect travel decisions by 43.4% (c) Partial test results of variables consisting of attractiveness, trustworthiness, expertise, which affect the awareness seen from the significant value is attractiveness. (d) Simultaneous test results of variables consisting of attractiveness, trustworthiness, expertise, travel decisions that affect awareness 23.8%. (e) The test results of the influence of a tour decision on awareness are influential with a significant value of 0,000 less than 0.05 at a 95% confidence level. (f) The results of the test of the influence of attractiveness, trustworthiness, expertise influencing Awareness through the Travel Decision as an intervening variable were found that the tour decision was an intervening variable due to an increase in the value of direct influence and from the results of testing through the variable of the travel decision.